CMR left ventricular strains beyond global longitudinal strain in differentiating light-chain cardiac amyloidosis from hypertrophic cardiomyopathy - Wang, Fangqing; Deng, Yan; Li, Shunjia; Cheng, Qichao; Wang, Qing; Yu, Dexin; Wang, Qian (Frontiers in Cardiovascular Medicine, 2023)
Background: The clinical value of left ventricular (LV) global longitudinal strain (GLS) in the differential diagnosis of light-chain cardiac amyloidosis (AL-CA) and hypertrophic cardiomyopathy (HCM) has been reported previously. In this study, we analyzed the potential clinical value of the LV long axis strain (LAS) to discriminate AL-CA from HCM. Furthermore, we analyzed the association between all the LV global strain parameters derived from the CMR feature tracking (CMR-FT) and LAS in both the AL-CA and HCM patients to assess the differential diagnostic efficacies of these global peak systolic strains. Methods: Thus study enrolled 89 participants that underwent cardiac magnetic resonance imaging (CMRI), including 30 AL-CA patients, 30 HCM patients, and 29 healthy controls. The intra-observer and inter-observer reproducibility of the LV strain parameters including GLS, global circumferential strain (GCS), global radial strain (GRS), and LAS were assessed in all the groups and compared. Receiver operating characteristic (ROC) curve analysis was performed to determine the diagnostic performances of the CMR strain parameters in discriminating AL-CA from HCM. Results: The intra- and inter-observer reproducibility of the LV global strains and LAS were excellent (range of ICCs:0.907-0.965). ROC curve analyses showed that the differential diagnostic performances of the global strains in discriminating AL-CA from HCM were good to excellent (GRS: AUC=0.921; GCS: AUC = 0.914; GLS: AUC = 0.832). Furthermore, among all the stain parameters analyzed, LAS showed the highest diagnostic efficacy in differentiating between AL-CA and HCM (AUC = 0.962). Conclusion: CMRI-derived strain parameters such as GLS, LAS, GRS, and GCS are promising diagnostic indicators that distinguish AL-CA from HCM with high accuracy. LAS showed the highest diagnostic accuracy among all the strain parameters.